2010
DOI: 10.1080/10440046.2011.530903
|View full text |Cite
|
Sign up to set email alerts
|

Forests for Food Security and Livelihood Sustainability: Policy Problems and Opportunities for Small Farmers in Nepal

Abstract: In Nepal, many rural households need access to public forest resources to complement private resources for food and livestock production. However, current forest policies are largely directed at Environmental protection. The first part of this study identified the effect of current forest policy on livestock production using survey data from 259 households in three Nepal hill districts. The second part used a forestry-agriculture integrated model to examine alternative land use policies that could increase hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…The unsafe lands were managed as a common property and used together in forest and pasture production to meet the broader needs of communities and environments. The communities used multiple products and services of the common property to complement private resources and sustain livelihoods (Dhakal et al, 2011;Hobley, 1996). Products and services derived from the joint management complement farmland resources and contribute to sustaining the livelihoods of mountain people with small size of landholdings.…”
Section: The Importance Of Multipurpose Management Of Forests and Evomentioning
confidence: 99%
See 2 more Smart Citations
“…The unsafe lands were managed as a common property and used together in forest and pasture production to meet the broader needs of communities and environments. The communities used multiple products and services of the common property to complement private resources and sustain livelihoods (Dhakal et al, 2011;Hobley, 1996). Products and services derived from the joint management complement farmland resources and contribute to sustaining the livelihoods of mountain people with small size of landholdings.…”
Section: The Importance Of Multipurpose Management Of Forests and Evomentioning
confidence: 99%
“…Poor rural houses require forest products to complement their private resource and so sustain their livelihood because of possessing insufficient private land resources and a poor level of livelihood assets (Dhakal et al, 2011). Non-timber forest products are the main inputs to leverage their farm economic activities and the means to utilize their spare work time for income generation.…”
Section: The Importance Of Multipurpose Management Of Forests and Evomentioning
confidence: 99%
See 1 more Smart Citation
“…For example, forests in Nepal, which occupy 40 percent of the land area, have traditionally supplied inputs such as firewood, fodder/pasture, timber, charcoal and other non-wood products that are useful for rural households. However, recent Nepalese government policies, designed to protect forests, have reduced rural communities' access to local forest products and further marginalized poor people (Dhakal et al, 2011;Thoms, 2008;Shrestha and McManus, 2007;Maskey et al, 2006;Hjortso et al, 2006). (Kumar, 2002;Agrawal, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, individual household foregone revenues from an alternative land use or labor activity might be different to the average foregone economic rent from other land-use options; the trade-offs between these two perspectives of opportunity costs should be considered in the valuation and design of a BSM. Lessons learned from Nepal have shown that poor members who used to rely heavily on forest are compelled to reduce collection of forest products, especially fodder, fuelwood and grazing although well-off members can compensate for loss of these products from their private land (Dhakal et al 2011). Thus the cost of foregone use is higher for the poorest and leads to justification for inclusion of higher weighting for the poor and vulnerable in their BS scheme.…”
mentioning
confidence: 99%